Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

If $x, y,z \in \mathbb{R}$,
and if

$$ \left ( \frac{x}{y} \right )^2+\left ( \frac{y}{z} \right )^2+\left ( \frac{z}{x} \right )^2=\left ( \frac{x}{y} \right )+\left ( \frac{y}{z} \right )+\left ( \frac{z}{x} \right ) $$

Prove that $$x=y=z$$

share|improve this question

4 Answers 4

Let $p = a+b+c$, then $ab+bc+ca = \frac{1}{2}(p^2 - p)$ and $abc=1$. So $a,b,c$ are solutions to the equation $$x^3 - px^2 + \frac{1}{2} (p^2-p)x - 1 = 0$$ The discriminant is $(\frac{1}{2}(p^2-p))^2 - 4(\frac{1}{2}(p^2-p))^3 - 4p^3 - 27 + 18 p (\frac{1}{2}(p^2-p)) \ge 0$, since the roots are real. This is equivalent to $$p^6 - 4p^5 + 5p^4 - 22p^3 + 36p^2 + 108 \leq 0$$ But by calculus or other means, one can check that the left hand side has minimum 0 only at $p = 3$. Thus $p = 3$, and $ab+bc+ca = 3$, $abc = 1$. So $a,b,c$ are roots of $x^3-3x^2+3x-1 = (x-1)^3$, i.e. $a,b,c = 1$, i.e. $x=y=z$.

share|improve this answer

Let $$ a=\frac{x}{y} $$ $$ b=\frac{y}{z} $$ $$ c=\frac{z}{x} $$ Then $$abc=1$$ $$ a^2+b^2+c^2=a+b+c$$ which implies $$ (a-0.5)^2+(b-0.5)^2+(c-0.5)^2=0.75$$ I was struck up here, i would appreciate if any one helps me here

share|improve this answer
    
The triple completing-the-square is a great technique, but it doesn't look like the way to go here, partly because $0.75$ is disappointing, but mostly because you didn't use $abc=1$. –  vadim123 Apr 25 '13 at 3:54

A similar triple completing-the-square is helpful. Using your notation, $(a-1)^2+(b-1)^2+(c-1)^2+2(a+b+c)-3=a+b+c$. This rearranges to $(a-1)^2+(b-1)^2+(c-1)^2=3-(a+b+c)$. Hence $a+b+c\le 3$ since otherwise the sum of three squares would be negative. Consequently $a^2+b^2+c^2\le 3$.

Unfortunately, I don't have a cute trick for the opposite inequality. Let $x=a^2, y=b^2$. I want to minimize $f(x,y)=x+y+\frac{1}{xy}$, assuming $x,y>0$. Setting the partials equal to zero, I get $1-\frac{1}{xy^2}=0=1-\frac{1}{yx^2}$, which has unique solution $x=y=1$. (as $x,y$ approach either 0 or $\infty$, $f(x,y)$ grows without bound, so this is a minimum). Consequently $f(x,y)\ge f(1,1)=3$.

share|improve this answer
1  
Apply AMGM directly, you get $x+y+\frac{1}{xy} \ge 3$. –  user27126 Apr 25 '13 at 4:16
    
D'oh! Thanks @Sanchez –  vadim123 Apr 25 '13 at 4:16

Let $a=\frac{x}{y}, b=\frac{y}{z}, c=\frac{z}{x}$, and let $$ G=\sqrt[3]{abc}, A = \frac{a+b+c}{3}, Q=\sqrt{\frac{a^2+b^2+c^2}{3}} $$ Then the given condition is $Q^2=A$, but by the power mean inequality $$ Q^2\ge Q \ge A \ge G = 1 $$ with equality in each case only if $a=b=c=1$, i.e. if $x=y=z$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.